2018
DOI: 10.1515/secm-2018-0170
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of Cu2O/ZnO nanocomposite for the decomposition of methyl orange under visible light irradiation

Abstract: ZnO is modified by Cu2O by the process of precipitation and calcination. X-ray diffraction has shown that Cu2O/ZnO catalysts are made of highly purified cubic Cu2O and hexagonal ZnO. Scanning electron microscopy and transmission electron microscopy have shown that ZnO adhered to the surface of Cu2O. Due to the doping of Cu2O, the absorption range of the Cu2O/ZnO catalyst is shifted from the ultraviolet to the visible region due to diffuse reflection. X-ray photoelectron spectroscopy and photoluminescence spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…From the CuS QDs @ ZnO XRD pattern, as the (107) and (103) planes of CuS appeared at 47.9° and 31.8°, respectively, and the (102) and (002) planes of ZnO appeared at 47.8° and 31.7°, it is observed that the CuS peaks at 31.78° and 47.64° are merged with ZNR peaks with a slight displacement. The small displacement between the (107) plane of CuS and the (102) plane of ZnO can confirmed the existence of lattice interaction, implying the formation of p-n heterojunctions 50 , 51 .…”
Section: Resultsmentioning
confidence: 82%
“…From the CuS QDs @ ZnO XRD pattern, as the (107) and (103) planes of CuS appeared at 47.9° and 31.8°, respectively, and the (102) and (002) planes of ZnO appeared at 47.8° and 31.7°, it is observed that the CuS peaks at 31.78° and 47.64° are merged with ZNR peaks with a slight displacement. The small displacement between the (107) plane of CuS and the (102) plane of ZnO can confirmed the existence of lattice interaction, implying the formation of p-n heterojunctions 50 , 51 .…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, the exploitation of a ZnO/Cu 2 O heterojunction is expected to slow down the charge carrier recombination rate-since there exists an irreversible electric field at the p-n junction of the ZnO/Cu 2 O system-and expand the absorption spectrum toward the visible light range, as shown in previous articles [8][9][10][11]. Furthermore, the concordance between the energy level and the electronic structure in the ZnO and Cu 2 O forms a superior catalytic p-n system compared with other p-n systems [8][9][10][11][12][13]. On the other hand, the formation of a Schottky barrier at the precious metal-semiconductor interface can efficiently prevent the recombination of electron-hole pairs [14][15][16].…”
Section: Introductionmentioning
confidence: 83%
“…Wang et al. fabricated p‐Cu 2 O−n‐ZnO nanoparticle heterojunctions through precipitation and calcination methods, 40 and their samples exhibited superior degradation efficiency of MO compared with Cu 2 O and ZnO alone under visible‐light irradiation. Hsiao et al.…”
Section: Introductionmentioning
confidence: 99%
“…7 The sample exhibited excellent photodegradation of methyl orange (MO) under visible-light irradiation. Wang et al fabricated p-Cu 2 O−n-ZnO nanoparticle heterojunctions through precipitation and calcination methods, 40 and their samples exhibited superior degradation efficiency of MO compared with Cu 2 O and ZnO alone under visible-light irradiation. Hsiao et al reported the synthesis of ZnO−Cu 2 O on Si nanowires (SiNWs) (supporting skeleton) using all-solution-based approaches.…”
Section: Introductionmentioning
confidence: 99%